Pola Penggunaan Levofloxacin pada Pasien HIV dan AIDS di UPIPI RSUD DR. Soetomo Surabaya - Pambudi, Rien Esti; Triyono, Erwin Astha; Surdijati, Siti; Jaya, Halim Priyahau (Jurnal Farmasi Sains dan Terapan, 2018)
HIV is a retrovirus (RNA) that attacks the human immune system. AIDS is a retrovirus disease characterized by immunosuppression which causes opportunistic infectious diseases. Opportunistic infections appear with new forms of infection by other microorganisms or reactivation of latent infections under normal conditions that can be controlled by the immune system so as not to cause manifestations. Opportunistic infections show effects on immunity associated with CD4 cell counts. The therapy used to reduce opportunistic infections is levofloxacin. Based on research, levofloxacin for HIV AIDS patients is often used to reduce opportunistic infections including bacterial pneumonia, tuberculosis and sepsis. This study aims to provide data that includes levofloxacin therapeutic doses, frequency use, old route drugs, prevalence and interaction of qualitative analysis related to medical records in HIV & AIDS patients at UPIPI DR. Soetomo Regional General Hospital Surabaya. The research method used is a retrospective observational study on medical records of patients with HIV & AIDS. Sampling was done by consecutive sampling in the period January 1, 2015 to June 30, 2015. The results obtained from the most relevant types of research, dose, frequency and route were levofloxacin for the treatment of opportunistic infections, especially bacterial pneumonia, tuberculosis, and sepsis. in oral doses and injections at a dose of 500 mg and a frequency of 750 mg 1x1. The use of levofloxacin given to HIV & AIDS patients at UPIPI DR. Surabaya Soetomo Regional General Hospital, related to dosage, route, frequency, interval, and duration of administration is in accordance with existing guidelines.